PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR), DISCLOSURE BREADTH, DAN DISCLOSURE DEPTH TERHADAP CORPORATE FINANCIAL PERFORMANCE: PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR), DISCLOSURE BREADTH, DAN DISCLOSURE DEPTH TERHADAP CORPORATE FINANCIAL PERFORMANCE - Rifka Kurnia Indah Saputri; Febrial Pratama (Jurnal Akuntansi Bisnis dan Ekonomi, 2020)
One of the companies that has good quality can be judged by looking at the Corporate Financial Performance (CFP) of a company. CFP is the result that has been achieved by the company management in carrying out its duties and functions effectively and efficiently by using proper and correct financial implementation rules. In this study, the ratio used to measure CFP is Earnings Before Interest Tax Depreciation and Amortization (EBITDA).This study aims to determine the disclosure of Corporate Social Responsibility (CSR) using the GRI G4 standard, Disclosure Breadth in disclosing the CSR theme and Disclosure Depth in sentences that are recorded based on interested parties (stakeholders) on CFP (EBITDA) in non-public state-owned oil companies and gas listed in OK Stock for the period 2011-2018.The population in this study were non-public state-owned oil and gas companies listed in OK Stock for the period 2011-2018. The sample selection technique used purposive sampling and obtained 4 non-public state-owned oil and gas companies over a period of 8 years so that 32 samples were observed. The data analysis method in this research is panel data regression using Eviews 10 software.The results showed that simultaneously CSR disclosure, disclosure breadth and disclosure depth have an effect on CFP. Partially disclosure breadth and disclosure depth do not have a significant effect, while CSR disclosure has a significant positive effect on CFP.Based on these results, stakeholders need to pay attention to the composition of CSR disclosure, both in terms of the breadth of disclosure and the depth of disclosure of the company so that the company can convince stakeholders to minimize the risks that will occur, maximize profitability and the objectives of all parties. reached.